An Autonomist Biopolitics of Education: Reproduction, Resistance, and the Specter of Constituent Bíos. Issue 3 (3rd January 2020) - Bourassa, Gregory N.
Abstract: In considering the enigmatic relationships between philosophy, politics, and pedagogy, this essay attempts to map some of the currents in educational scholarship, particularly those running between reproduction theories and resistance theories. While these two theoretical frameworks have been at odds with one another, Gregory Bourassa suggests that both share orthodox commitments that prevent them from appreciating the constituent dimensions of revolutionary subjectivity. In seeking an alternative orientation, Bourassa proposes an autonomist biopolitics of education. This framework inverts the traditional circuits of resistance and suggests that schools follow behind and resist the constituent life forms (constituent bíos ) of students. If resistance theory only attempts to identify the ways in which students resist school practices, it risks obscuring the potentiality of constituent bíos as a social ontology that is primary, always already present, and subject to the resistant practices of the school. Therefore, a key contribution of this essay is its development of an autonomist biopolitics of education. Within this framework, constituent bíos is recognized as the foundational and constitutive motor to which schools are constantly reacting. The adoption of this perspective, alongside more conventional understandings of resistance, offers a more nuanced conception of the relation between forms of life and schools.